A community intervention effectiveness study of single dose or two doses of bivalent HPV vaccine (CERVARIX®) in female school students in Thailand. - Suchada Jiamsiri; Chulwoo Rhee; Hyeon Seon Ahn; Nimesh Poudyal; Hyeong-Won Seo; Worrawan Klinsupa; Pornjarim Nilyanimit; Nakorn Premsri; Chawetsan Namwat; Sompong Vonpunsawad; Yun Chon; Sunju Park; et al. (PLoS ONE, 2022)
Human papillomavirus (HPV) is a common infection principally spread through sexual activity. Most HPV infections are asymptomatic and resolve spontaneously. However, persistent infection may progress to cervical cancer. Highly efficacious HPV vaccines have been available since 2006, yet uptake into national programs has been slow in part due to cost. WHO guidelines call for a two-dose (0,6 month) schedule for girls 9-14 years of age. Post-hoc analyses of randomized trials have found high vaccine effectiveness following a single dose of vaccine. In order to provide additional data on the potential impact of single dose HPV vaccination in a real-world setting, we are conducting an effectiveness study among Thai schoolgirls. This is an observational study of a single dose (SD) or two doses (2D) of the bivalent HPV vaccine CERVARIX® (GlaxoSmithKline plc.) administered in a school-based program to 8-9,000 Grade 8 female students in two provinces of Thailand beginning in 2018; one province is assigned the SD, and the other the standard 2D regimen. The reduction in HPV vaccine-type prevalence will be assessed in each province two and four years after vaccination by comparing HPV prevalence in urine samples obtained through cross-sectional surveys of the immunized grade cohort as they age and compared to a historical "baseline" HPV prevalence of same age students.